Relations between classroom disciplinary problems and student motivation: Achievement as a potential mediator?. (October 2015) - Arens, A. Katrin; Morin, Alexandre J.S.; Watermann, Rainer
Abstract: This study examined the relation between classroom disciplinary problems in language classes, student achievement, and three facets of student motivation: competence self-perceptions, test anxiety, and engagement. The analyses were conducted with the German sample from the Progress in International Reading Literacy Study (PIRLS) 2006 ( N = 7899). The results demonstrated that discipline problems are directly and negatively related to achievement and to all motivation constructs considered. In most cases, the relation between classroom disciplinary problems and motivation constructs was mediated by verbal achievement. Boys were found to report more frequent discipline problems in classrooms than girls. This study contributes to research by assessing the impact of classroom disciplinary problems using doubly latent multilevel structural equation models in order to properly disaggregate effects occurring at the student, versus classroom level. Highlights: Direct relations between disciplinary problems and motivation constructs. Indirect relations mediated through achievement (test scores and grades). Disentangling effects on the individual student and classroom levels. Gender differences in perceptions of disciplinary problems.